EXPLORING TEAM COHESION IN PROJECT MANAGEMENT - Denisa Maria COJOACĂ (ALNIȚI) (Management & Marketing)
Project management represents an essential area of research with a significant impact on society and the economy. This paper aims to critically analyze the scientific literature on team cohesion and its influence on project outcomes. We employ a qualitative approach based on secondary sources to identify and evaluate critical factors such as knowledge exchange, trust, and team cohesion and to examine how these contribute to project success. The novelty of our work lies in its interdisciplinary approach, integrating perspectives from organizational psychology and project management to investigate the dynamics of team cohesion and its impact on project performance. Within this article, we critically analyzed team cohesion through the lens of individual team member competencies first, leadership styles second, and the relationship between them third. Our results indicate that integrating team cohesion into project dynamics maximizes operational efficiency and enhances resilience and adaptability against unexpected challenges. Managers who adopt specific leadership approaches (e.g., transformational and transactional) are identified as crucial factors in creating and maintaining project team cohesion. Furthermore, the article emphasizes that integrating team cohesion into management practices contributes not only to project success but also to its sustainability. Managers can develop effective strategies and interventions to enhance collaboration and outcomes within project teams by profoundly understanding the relationship between team cohesion and project performance.